Modelling and Control of Mechatronic and Robotic Systems, Volume II - Gasparetto, Alessandro; Seriani, Stefano; Scalera, Lorenzo (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
In modern times, mechatronic and robotic systems are developing at a faster pace than in the past, and research on novel solutions and applications of such devices are studied in both industrial and academic environments. The second volume of this Special Issue of Applied Sciences aims to disseminate the latest research achievements, ideas, and applications of the modeling and control of mechatronic and robotic systems, with particular emphasis on novel trends and challenges. We invited contributions to this Special Issue on topics including (but not limited to): modeling and control, path and trajectory planning, optimization problems, collaborative robotics, mechatronics, flexible multi-body systems, mobile robotics, and manufacturing applications.